LAJU INFILTRASI DAN PERANANNYA TERHADAP PENGELOLAAN DAERAH ALIRAN SUNGAI ALLU-BANGKALA - Syamsul Syukur (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The objective of the research was to identify the rate and amount of soil water infiltration under various soil characteristics in the Sungai Allu Bankala Watershed.  Data of the measurement can assist to indicate water requirement for different soil types to achieve certain soil humidity. This water requirement can be given by irrigation or precipitation. The research was done in non irrigated paddy or corn land at the Sungai Allu Bankala Watershed, sub district Bangkala District - Jeneponto , South Sulawesi. The types of  soils tested and replication done as follow : Grey Alluvial (2  replications) ; Litosol (3  replications) ; Red Brown Latosol (3 replications ); and Association of litosol and Red Mediteran (2 replications). So that there are 10 location observed. The measurement of infiltration was done using a double ring infiltrometer with measurement interval of 5-6 hours. The results showed that the constant infiltration was achieved after 4-5 hours. The determination coefficient value at linier and non-liniar curve were > 0.9 indicating that the value was sufficiently accurate. The average of infiltration from the highest to the lowest values were as follows Grey Alluvial>Litosol > Association of Latosol and Litosol > Mediteran – Litosol. The first two soil types had very rapid infiltration rate category, while the last two soil types was moderate. The time to achieve a constant infiltration rate under the non irrigated paddy land planted with paddy/corn was faster than other soil condition.